ВЫСОКОТОЧНАЯ КВАЗИИТЕРАЦИОННАЯ ДВУХКАНАЛЬНАЯ ЭЛЕКТРОМЕХАНИЧЕСКАЯ СИСТЕМА С МЕХАНИЧЕСКИМ ДИФФЕРЕНЦИАЛОМ - Худяев, А.А.; Кунченко, Т.Ю. (Інститут електродинаміки НАН України, Київ, 2015)
The mechanics’ kinematical diagram and mathematical model, kvazyiterative two-channel control system functional and block diagrams of the differential servodrive with channels standard tuning for high-precision metal-cutting machine tool workpiece feeding mechanism are considered. Electrical dynamics and accuracy characteristics computer simulation results are provided. Considerable advantages of rapidity control accuracy of the presented two-channel servodrive as compared to the common one-channel feeding mechanism servodrive are presented. The advantages of the two- channel servodrive due to the low power of on additional (precise) control channel can only be realised in the range of minor and partially, medium displacement of the workpiece. References 8, tables 2, figures 6.